Bisphenol A-Induced Epigenetic Changes and Its Effects on the Male Reproductive System - Cariati, Federica; Carbone, Luigi; Conforti, Alessandro; Bagnulo, Francesca; Peluso, Stefania Ramona; Carotenuto, Consolata; Buonfantino, Cira; Alviggi, Erminia; Alviggi, Carlo; Strina, Ida (Frontiers in Endocrinology, 2020)
Bisphenol A (BPA) is a widespread chemical agent which can exert detrimental effects on male reproductive system. Exposure to BPA has been shown to induce several epigenetic modifications in both animal and human cells. Specifically, BPA could modify the methylation pattern of multiple genes encoding proteins related to reproductive physiology, but could also directly influence the genes responsible for DNA methylation. BPA effects include hormonal alterations, micro- and macroscopic alteration of male reproductive organs and inheritable epigenetic changes involving human reproduction. BPA exposure was also linked to prostate cancer. This review aims to show the current scenario of BPA-induced epigenetic changes and its effects on male reproductive system. Possible strategies to counter the toxic effect of BPA were also addressed.